The Integration of Aqidah, Akhlaq, and Adab in Aqidah–Akhlaq Education through the Exemplary Narratives of the Prophet and the Rightly Guided Caliphs in the Digital Era - Abdullah Abdullah; Husnul Khotimah; Aysah Aysah; Elva Oktavia (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Aqidah Akhlak education plays a crucial role in shaping faithful, moral, and well-mannered students. An effective method in this learning is utilizing exemplary stories of prophets and companions. This study aims to analyze the integration of aqidah, akhlak, and adab elements in the stories of Prophet Yunus, Prophet Ayyub, Prophet Dawud, Prophet Sulaiman, and the Khulafaur Rasyidin. Using a qualitative library research method, this study analyzes textbooks and relevant academic literature. The findings show that each exemplary story contains aqidah as a foundation of faith, fostering noble qualities (patience, gratitude, repentance, justice, and trustworthiness) which manifest in polite and responsible conduct. This integrative pattern forms a holistic and balanced Muslim character. Thus, exemplary stories are effective media for character education as they integrate students' cognitive, affective, and psychomotor aspects.